2018
DOI: 10.1007/s00382-018-4095-5
|View full text |Cite
|
Sign up to set email alerts
|

On the link between the subseasonal evolution of the North Atlantic Oscillation and East Asian climate

Abstract: We analyse the impact of the North Atlantic Oscillation (NAO) on the climate of East Asia at subseasonal time scales during both winter and summer. These teleconections have mainly been investigated at seasonal and longer time scales, while higher-frequency links are largely unexplored. The NAO is defined using extended empirical orthogonal functions on pentad-mean observations, which allows to elucidate the oscillation's spatial and temporal evolution and clearly separate the development and decay phases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 94 publications
2
47
0
Order By: Relevance
“…Previous studies have made much effort to investigate the connections between the NAO and the climate over East Asia (e.g. Watanabe 2004, Bollasina & Messori 2018. The spring NAO imprints its signals on the North Atlantic summer sea surface temperature anomalies and then triggers a baro -tropic teleconnection pattern over the North Atlantic and Eurasia, which is closely linked to the East Asian summer monsoon (Zuo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have made much effort to investigate the connections between the NAO and the climate over East Asia (e.g. Watanabe 2004, Bollasina & Messori 2018. The spring NAO imprints its signals on the North Atlantic summer sea surface temperature anomalies and then triggers a baro -tropic teleconnection pattern over the North Atlantic and Eurasia, which is closely linked to the East Asian summer monsoon (Zuo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2, the latter showing the five-pentad evolution of the 925-hPa wind anomalies obtained from lead/lag regressions on the EOF1-PC. The larger variance explained by the EOF1 (64.3%) compared to that of the EEOF1 (27.2%) is not surprising, since using a series of five spatial patterns instead of one in the covariance matrix increases the variance (Bollasina and Messori 2018). While the mature phase (lag 0) spatial pattern is very similar between both methods, the lead/lag EOF regressions do not capture the wind evolution at sub-monthly timescale (from its nascent to its decay phase) entirely, but, instead, depict a strong dominance of higher-frequency (supersynoptic) variability.…”
Section: Spatio-temporal Evolution Of the Clljmentioning
confidence: 97%
“…1 shows the May to June 925-hPa wind climatology, the topography of the region and the Caribean domain used for the EEOF enclosed in a box. The EEOF technique is a useful tool to analyse geophysical fields given their high spatio-temporal co-variability and has been successfully used in hydroclimate and teleconnection analyses recently (e.g., Weaver and Nigam 2011;Baxter and Nigam 2015;Bollasina and Messori 2018). This method extracts the most recurrent temporal series of spatial variability patterns associated with each principal component (PC), with no assumption or imposition of any specific periodicity.…”
Section: Extended Empirical Orthogonal Function Analysismentioning
confidence: 99%
“…This teleconnection pattern, which originates in the subtropical North Atlantic, is different from the pattern with the Asian jet waveguide path and was first termed the “North Atlantic‐Eurasian teleconnection pattern” by Li and Ruan (). The summer NAO variation has been shown to influence large‐scale summer precipitation anomalies over East Asia via this teleconnection pattern (Bollasina & Messori, ; Folland et al, ; Linderholm et al, , ; Liu & Yin, ; Zheng et al, ). Significant negative correlations between the teleconnection pattern index and summer precipitation were found in northern China.…”
Section: Introductionmentioning
confidence: 99%
“…For example, remote influences of the NAO on the interannual variability in summer precipitation in eastern China have been explored to some extent. Early studies on this subject have focused on the influence of the winter or spring NAO (Bollasina & Messori, 2018;Fu & Zeng, 2005;Gu et al, 2009;Sung et al, 2006;Tian & Fan, 2012;Wu et al, 2009Wu et al, , 2012Yang et al, 2004;Zheng et al, 2016;Zuo et al, 2012) and have suggested that their influence on East Asian summer precipitation is chiefly via the subtropical Asian jet waveguide-trapped wave train (e.g., Bollasina & Messori, 2018;Sung et al, 2006). Recently, a high-latitude remote climatic teleconnection in summer in eastern China from the North Atlantic Ocean has garnered considerable attention.…”
Section: Introductionmentioning
confidence: 99%